Irony to Educate in Sustainability: From Self-care to Caring for Others and the Common Home - Chiara Carletti (Pensa MultiMedia, 2022)
The pandemic crisis has spared no sector of society: economic, political, social or educational. Since economic and educational poverty feed on each other, in the last two years children and adolescents have been deprived of many opportunities related to learning, socialization, cultural enjoyment and play. In particular, extracurricular, physical and recreational activities have disappeared, and so schools and the entire educational community have lost the fundamental function of forming people with solid and conscious identities, capable of choosing their own future. After months of closures and restrictions, young people must once again take the lead in their own lives, learning to deal with the complexity of reality through a self- and worldawareness. This is essential to create an educational outlook that can make them not only persons, but also critical and active citizens within a community in which everyone pursues not only their own well-being, but also the common good. Hence, the category of education needs to be given renewed centrality in order to affirm a new anthropology in which citizenship, participation and reciprocity become planetary-wide and the acquisition of a critical, ironic and capacitating forma mentis can guide a new model of sustainable development.